IMPLEMENTASI LANDASAN PENGEMBANGAN KURIKULUM DALAM PEMBENTUKAN KARAKTER SISWA SDIT - Hendrizal; Reni Deswita Sari; Lusi Andalusia; Nira Regina; Julmadi; Delmi Yunita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the foundations of curriculum development and their application in character building at SDIT Mutiara Hati, Payakumbuh City. The problem addressed is the limited research on how the integration of three curricula aligns with the five main curriculum foundations to foster student character in a local context. This research adopts a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The results show that the curriculum development at this school is firmly based on religious, philosophical, juridical, psychological, and sociological aspects. The implemented curriculum successfully integrates the Independent Curriculum, the Ministry of Religious Affairs Curriculum (MDTA), and the JSIT Curriculum. Character education is systematically implemented through classroom learning, routine activities, school culture, and extracurricular programs. Consequently, the developed character values among students include religiosity, honesty, discipline, responsibility, cooperation, and noble morals. Accordingly, a comprehensive curriculum foundation significantly contributes to shaping students who are faithful, possess noble character, and excel in their achievements.